Imaging of the Biliary Tract - Achmad Nurman (The Indonesian Society for Digestive Endoscopy, 2010)
Imaging is central to the investigation and diagnoses of biliary tract disease. Upper abdominal pain, jaundice and abnormal liver function test are common symptoms and signs and imaging of the biliary tract should be performed to make an exact diagnosis of the disease. There are many options in the field of imaging from simple to more sophisticated examinations. Several imaging techniques are obsolete namely oral cholecystography, Intravenous cholangiography and biliary scintigraphy, and should therefore be omitted. These imaging techniques are expensive and we should choose one or two options. Abdominal ultrasound is less expensive and can be performed rapidly without special preparation or contrast agent. It is the imaging of choice in the initial evaluation to evaluate patients with hepatopacreaticobiliary diseases. From the Result of abdominal ultrasound examination we can choose further the right imaging technique that can disclose the diagnoses of the disease.Keywords: biliary tract, diseases, imaging